The Ineffectiveness of ASEAN Political Security Community Blueprint in Promoting Shared Responsibility for Comprehensive Security in Counterterrorism: Case Study Terrorism in Tri-Border Area of Indonesia, Malaysia, and Philippines 2009-2018 - Indra Setiawan; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2019)
Tri-border area of Indonesia, Malaysia, and Philippines are facing the threat of terrorism as a result of terrorist activities by Abu Sayyaf and Moro Islamic Liberation Front. ASEAN countries have countered the threat by undertaking joint military cooperation. However, this research found that the security cooperation is not in line with the principle of shared responsibility for comprehensive security stipulated in ASEAN Political Security Community (APSC) Blueprint. This research aims to explain the causes of APSC Blueprint‘s ineffectiveness in promoting shared responsibility for comprehensive security to counter terrorism in tri-border area. This research addresses this question by using qualitative method where secondary data from journals, books, official documents, and reports are utilized. Using the theory of compliance and concept of legalization, this research answers the question by examining the institutional design of ASEAN Political Security Community Blueprint. This research found that there is a compliance problem in APSC Blueprint consisting of failure of obligational clarity, failure of performance clarity, and failure of response clarity. In addition, the ASEAN Political Security Community Blueprint falls into the category of low legalization, making this blueprint is non-binding. Therefore, the violations to the commitment stipulated in the blueprint will not result in significant consequences.